Palestine Radar Model (PRM) for Predicting the Number of Infected Cases of COVID-19 Virus in Palestine - Abu Omar, Dr. Mohammad (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
In the light of the COVID-19 virus pandemic that has attacked the earth planet, all nations in the world are becoming suffered more and more from the increasing number of infected cases. The medical infrastructure in most countries aren’t fit to deal with such pandemic, hospitals in these countries are unable to accommodate a such number of the infected cases that have recently been recorded[1],[5]. This pandemic has put countries in a great predicament; they never expected to face a pandemic of this size [1], [5]. Palestine is one of these pandemic victims, COVID-19 virus has started spreading in Palestine on fifth March of 2020 [4]. Palestinian government and leadership have announced immediately by its Prime Minister Dr Mohammad Shtayyeh the case of emergency in Palestine to prevent this dangerous pandemic from spreading, by closing all schools and universities, crowding prevention, limiting motion and asking people strongly for home-stay [1], [2], [4]. With this step, Palestine has been recorded as one of the most quick-response countries of facing the COVID-19 pandemic in the world [4]. Although the emergency case is still very active in Palestine, the Palestine government and people are still very worry and afraid from the coming future, this is for two main reasons, the first is the inability of Palestine medical infrastructure to process the large numbers of infected cases, the second is the social-cultural system in Palestine that has strong relationships and traditions that promotes social communication in Palestine which may help the COVID-19 virus for more spreading. So, this study aims to help Palestinian government to be ready as possible to face this pandemic in the coming days, by designing a computerized model to predict the expected numbers of the infected cases that may be recorded in the coming days.